حديث قطع يد المستعير، إشكالية، أسباب، وحلول (The Hadith of Cutting off the Borrower's hand, Problem, Reasons, and Solutions) - علي, نوح; منصور, سعد الدين (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
يهدف هذا البحث إلى توضيح الاشكال لحديث قطع يد المستعير، ففي ظاهر الحديث هناك إشارة تدل على إشكالية في المعنى الحديث، فالبحث يقوم بذكر الحديث أولاً، وتخريجه، ثم بيان حكمه من حيث الصحة والضعف، وذكر أقوال العلماء فيه والمقصود منه، وإزالة الإشكال الوارد، وبيان عدم التعارض بينهما. وتكمن إشكالية هذا البحث في عدم فهم هذا الحديث، فجاء هذا البحث لدراسة هذه الإشكالية، وحلولها بكلام أهل العلم في المقصود من الحديث، وتبرز أهمية هذا البحث في حاجة الناس إلى فهم أمثال هذه الأحاديث وتطبيقها وفق المنهج الشرعي. وقد اعتمد البحث المنهج الاستقرائي في ذكر روايات الحديث الواردة، والمنهج الوصفي التحليلي في بيان المراد منه، وبيان عدم الإشكال والتعارض فيه، والمنهج النقدي في تمييز الأحاديث الواردة في الباب من حيث الصّحة والضعف. ومن أهم النتائج الإشكال الموجود في الأحاديث لم يصل إلى درجة التعارض الحقيقي بين النصوص الشرعية، لأن الشريعة لا تعارض فيها، ولا تجد دليلين أجمع المسلمون على تعارضهما. الكلمات المفتاحية: قطع، المستعير، الإشكال، رفع التعارض. Abstract The research aims to clarify the forms of the hadith of cutting off the borrower’s hand. In the apparent meaning of the hadith, there is a sign indicating a problematic in the modern meaning. The research first mentions the hadith, extracts it, and then explains its ruling in terms of health and weakness, and mentions the sayings of scholars about it and what is meant by it, removing the incoming problems, and clarifying There is no conflict between them. The problem of this research lies in the lack of understanding of this hadith, so this research came to study this problem, and its solutions according to the words of the scholars regarding the purpose of the hadith. The research adopted the inductive method in mentioning the hadith narrations mentioned, the descriptive analytical method in clarifying what is meant by it, the lack of confusion and contradiction in it, and the critical method in distinguishing the hadiths contained in the chapter in terms of validity and weakness. One of the most important results is the confusion found in the hadiths, which did not reach the degree of real conflict between the legal texts, because Sharia does not contradict it, and you do not find two evidences that Muslims are unanimously in conflict with. Keywords: Cutting, Borrowing, Confusion, Lifting of conflicts.